Explosion pressure of industrial titanium powder and its suppression characteristics by explosion suppressants SiO2, K2CO3, and NaHCO3 - Tianqi Liu; Kenan Liu (Scientific Reports)
Abstract The ignition and explosion risks of industrial metal powder are significantly different from other types of powder, and its explosion suppression deserve attention. In this article, industrial titanium powder explosion is taken as the test object, and its explosion pressure and explosion suppression process are analyzed. The research results show that the mass concentration of powder clouds and ignition delay time have a great impact on the explosion pressure of titanium powder. The optimal concentration of powder cloud mass is 350 g m−3, under this condition, the rate of energy release per unit time is the highest, the maximum pressure of titanium powder explosion is 0.48 MPa. The optimal ignition delay time is 50 ms, changing the ignition delay time actually changes the state of the powder cloud at the ignition moment. The suppression effect can be ranked, and the best suppression agent is NaHCO3, followed by K2CO3, and finally SiO2. Under the effects of isolation, dilution, and cooling, NaHCO3 has the greatest effect on the explosion pressure of titanium powder.